2020
DOI: 10.1371/journal.pone.0235557
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydration status on plasma FGF21 concentrations in humans: A subanalysis of a randomised crossover trial

Abstract: Aim Fibroblast growth factor 21 (FGF21) has recently been implicated in thirst in rodent models. The mechanisms for this are currently uncertain, and it is unclear whether hydration status can alter FGF21 concentrations, potentially providing an additional mechanism by which hypohydration induces thirst. The aim of this study is therefore to understand whether hydration status can alter circulating FGF21 in humans. Methods Using a heat tent and fluid restriction, we induced hypohydration (1.9% body mass loss) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We also previously found that FGF21 administration does not acutely increase total fluid intake in a two-bottle choice assay with or without sucrose (Flippo et al, 2020). Importantly, physiological plasma FGF21 levels are not significantly altered by hydration status (Carroll et al, 2020). We instead hypothesize that observed effects of FGF21 on water intake in mice may occur secondarily to FGF21's effects on energy expenditure (Camporez et al, 2013) and prandial thirst (BonDurant and Potthoff, 2018).…”
Section: Discussionmentioning
confidence: 76%
“…We also previously found that FGF21 administration does not acutely increase total fluid intake in a two-bottle choice assay with or without sucrose (Flippo et al, 2020). Importantly, physiological plasma FGF21 levels are not significantly altered by hydration status (Carroll et al, 2020). We instead hypothesize that observed effects of FGF21 on water intake in mice may occur secondarily to FGF21's effects on energy expenditure (Camporez et al, 2013) and prandial thirst (BonDurant and Potthoff, 2018).…”
Section: Discussionmentioning
confidence: 76%
“…Increased levels of corticotropin-releasing hormone or corticosterone/cortisol with FGF21 or FGF21 analog treatment have been reported in rodents, but not in non-human primates nor in any human studies (183,293,313). Likewise, reports of FGF21 increasing water intake and blood pressure in rodents, potentially by stimulating sympathetic pathways (313, 314) do not appear to translate consistently to humans, with one study (293) but no others (183,(244)(245)(246)315) suggesting an effect. The lack of effect is consistent with blood pressure phenotypes of humans with FGF21 genetic variants.…”
Section: Safety and Tolerability Of Fibroblast Growth Factor 21 Analomentioning
confidence: 99%
“…This hormone is also implicated in thirst and increases drinking in animal models (Turner et al 2018), and thus may proffer an explanation towards the higher water intake in those with a sweet tooth. However, evidence in humans is inconclusive as hydration status has not been shown to alter fasting plasma fibroblast growth factor 21 concentrations, though drinking behaviours have not been measured (Carroll et al, 2020b). Further research might investigate interactions between thirst, sweet preference, and fibroblast growth factor 21.…”
Section: Resultsmentioning
confidence: 99%